How aware is the public of the existence, characteristics and causes of language impairment in childhood and where have they heard about it? A European survey - Thordardottir, Elin; Topbaş, Seyhun; Argus, Reili; Blahova, Veronika; Bulut, Talat; Camilleri, Bernard; Castro, Ana; Czaplewska, Ewa; Dabašinskienė, Ineta; Daniela, Linda; Dulcic, Adinda; Esposito, Anna; et al. (My University, 2021)
Public awareness of language impairment in childhood (Developmental Language Disorder (DLD)) has been identified as an important determiner of research and clinical service delivery, yet studies directly assessing public awareness are lacking. This study surveyed awareness across 18 countries of Europe. Method A questionnaire developed by an international team asked whether respondents had heard of language impairment affecting children, what they thought its manifestations and causes were and where they had heard of it. Respondents were also asked whether they had heard of autism, dyslexia, ADD/ADHD and speech disorder. The questionnaire was administered to members of the public in 18 European countries. A total of 1519 responses were obtained, spanning 6 age groups, 4 educational level groups and 3 income level groups. Results Across all but one country, significantly fewer people had heard of language impairment than any of the other disorders (or 60 % compared to over 90 % for autism). Awareness tended to be lowest in Eastern Europe and greatest in North-Western Europe, and was influenced by education level, age and income level. People in countries with overall low and overall high awareness differed in their views on manifestations and causes. People had heard of language impairment and autism the same way - most frequently through the media, including Internet, and less frequently through their child’s school or a medical professional. Discussion The study confirms that awareness of language impairment and knowledge of the breadth of its manifestations are low. It also suggests opportunities for how to increase awareness, including greater media coverage of language impairment and more efficient use of venues such as schools and healthcare. Ways in which cultural and linguistic differences may influence public awareness efforts are discussed, including the translatability of clinical labels and scientific terms. These may impact the acceptance of a common term and definition across all countries. As awareness campaigns are gaining momentum, the findings of this study can serve as a baseline against which to compare future findings.
Keywords: Language impairment; Children; Developmental language disorder; Awareness; Public; Europe